Pengemasan Produk Sayuran Dengan Bahan Kemas Plastik Pada Penyimpanan Suhu Ruang Dan Suhu Dingin - Dea Tio Mareta; Shofia Nur Awami (Universitas Wahid Hasyim, 2011)
Agricultural Product (both of raw material and intermediate good/ food) has limited durability before perish process. It relates with physicalcharacter of them, different with physical character of industrial product.The physical character are perishable , bulky, and voluminous. Onealternative that could be done, for fresh and good product when it is givento consumer is packing. Type of packing materials e g : plastic, glass,paper, and styrofoam. There are many packing technique : common,vacuum and press. From permeability calculation, is known if bahwa permeability of polypropylen plastic is bigger than polyethylen plastic. It isdeviation, because of polypropylene permeability must be lower thanpolyethylene. For application test on water spinach, permeability ofpolypropylen plastic is lower than polyethylen. The different ofPermeability on polypropylen and polyethylen packing impacts on weight,color, and texture of water spinach leaf. While on cold temperature packing,polypropylene plastic is better than polyethylene as material packing. Keywords : Packing, Polypropylene plastic, Polyethylene plastic.